Pengaruh Pemberian Terapi Kompres Dingin terhadap Penurunan Skala Nyeri pada Pasien Post Episiotomi - Puspitasari, RA Helda; Handayani, Dwining; Nastiti, Ayu Dewi; Umam, Esa Rosyida; Laily, Nurul Fahmi Rizka; Nafi'a, Abidatun; Jannah, Miftahul (Jurnal Gema Keperawatan, 2025)
Normal childbirth is a physiological process that can cause pressure on the perineal tissue, so that episiotomy is often required to prevent more severe tears, episiotomy can also cause pain that interferes with the comfort and recovery process of the mother. Pain due to episiotomy if not handled properly can inhibit early mobilization, prolong healing time, reduce sleep quality, and affect the bond between mother and baby. This study aims to determine the effect of cold compresses in reducing the pain scale in post-episiotomy mothers. This study used a pre-experimental design with a one-group pre-posttest design approach, this study was conducted at the Sahara inpatient primary clinic in Pasuruan City, the population in this study were all mothers who had normal deliveries and underwent episiotomy, with a sample size of n=20 responden. The inclusion criteria in this study were postpartum mothers on day 1 to day 3 who experienced pain due to episiotomy, were willing to participate in the intervention, and had no contraindications to cold therapy. Pain measurements were carried out using the Numeric Rating Scale (NRS) and were measured before and after the intervention. Data analysis using a chi-square test showed a p-value of 0,011 (p0,05) indicating a significant difference between before and after the intervention. These findings demonstrate that cold compresses effectively reduce post-episiotomy pain in mothers. This intervention can be a safe, easy-to-implement, and beneficial non-pharmacological therapy alternative in accelerating the recovery process and improving the quality of life of postpartum mothers.